Short Communication: Waterbird species distribution between natural and manmade wetland in Himalayan foothills of Uttarakhand, India - VIKAS SAINI; KAMAL JOSHI; DINESH BHATT; ASHUTOSH SINGH; RITESH JOSHI (Society for Indonesian Biodiversity, 2017)
Abstract. Saini V, Joshi K, Bhatt D, Singh A, Joshi R. 2017. Short Communication: Waterbird species distribution between natural and manmade wetland in Himalayan foothills of Uttarakhand, India. Biodiversitas 18: 334-340. A comparative study on waterbird diversity and abundance was conducted at natural and man-made wetland of District Hardwar from 2010 to 2013. A total of 37 waterbirds belonging to 11 families were recorded of which 14 species were winter migrant in the wetlands of the study area. Among these waterbird species, two species viz. Black-necked Stork, Ephippiorhynchus asiaticus; River Lapwing, Vanellus duvaucelii were near threatened (IUCN status Ver. 2013.1.) and two species namely Woolly-necked Stork, Ciconia episcopus; andÂ  Marbled Duck, Marmaronetta angustirostris were Vulnerable (IUCN status). The avian species diversity and abundance were recorded significantly high (t = 4.16, p < 0.01) at natural wetland site. It is also observed that vegetation variety and food availability is the responsible causes of waterbird species variation in the natural and manmade wetland. The results of this study suggest that freshwater natural wetland site is more suitable habitat for short and long-distance water migratory birds. This natural wetland should be protected to enhance the abundance and diversity of water migrant community. Keywords: Diversity, man-made wetland, migratory species, natural wetland